Evaluation of ecological and genetic condition of Rivne city for Micronucleus Test - Grygus, Igor; Kaskyv, Mariana; Zukow, Walery (Ecological Questions, 2018)
Bioindication evaluation of air condition in the city of Rivne has been carried out using the micronucleus (MN) test on the oral mucous in under-school-age children. The highest maximum values of MN indices were determined for children who live in the studied test ranges, where the content of CO (carbon oxide) exceeds the maximum permissible concentration. Cytogenetic indicators vary in a wide range of numerical values; moreover, the level of cytogenetic damage is an informative bioindicational feature. With the monitoring purpose, the researched urban area of Rivne was divided into 12 test ranges with different anthropogenic load; a number of large and small manufacturing firms are situated there. The analysis of statistical and analytical data on the traffic intensity in the city was conducted. The study was also based on the analysis of personal researches, obtained through a comprehensive survey carried out on 167 children in 12 test ranges in 12 preschools, the average age of children was 6-7 years. A total of 64,950 mucosal epithelial cells were explored. It has been shown that the deterioration of ecological and genetic conditions of the urban environment in test ranges I, II, VI, VII, VIII, XI based on the cell damage level was "below average", the condition of the children’s organism was "alarming" but the state of the environment has changed from “excellent” to “satisfactory”. This kind of research can enable observations of the mutagenic background of regions, genetic health, and genetic threats to humans due to harmful factors.